Single incision laparoscopic surgery (SILS™) using an umbilical hernial approach for cryptorchidectomy of a degenerated testis in a dog - de Faria Tiosso, Caio [UNESP]; Voorwald, Fabiana Azevedo; Brun, Maurício Veloso; Nakaghi, Luciana Cristina Padilha [UNESP]; Crivelaro, Roberta Martins [UNESP]; Apparicio, Maricy [UNESP]; Vicente, Wilter Ricardo Russiano [UNESP] (FapUNIFESP (SciELO), 2019)
SILS™ via an umbilical hernia opening was used in the correction of an abdominal cryptorchidism in a dog. The SILS™port was inserted through a 2.5 cm skin incision on the umbilical hernia and pneumoperitoneum was established with CO2. A 10mm telescope, 5mm laparoscopic Babcock clamp, and a clamp with combined cutting and coagulation features were used for the dissection and removal of the testicle through the SILS™ port. The treatment proved to be effective, easy, and quick to perform. However, the lack of triangulation between clamps and telescope limited the movement of the instruments, making it more laborious than a multiple-trocar approach. It can be concluded that the use of a SILS™ port through a pre-existing opening of the abdominal wall enables a reduction of the risks associated with multiple incisions; such as injury and manipulation of internal organs, pain, bleeding, and development of new hernias.
Aplicação do portal único (SILS™) por acesso herniário umbilical para criptorquidectomia de testículo degenerado em cão
Keywords: Canine; Cryptorchidism; Laparoscopy; Sils; Single-port